PENDIDIKAN MATEMATIKA DI SEKOLAH KITA - Kamarullah, Kamarullah (Al-Khawarizmi, 2017)
Mathematics is constantly evolving in accordance with the human need for technology. Therefore, mathematics is a subject that is taught at each level of education, according to the needs of all levels of education. In Indonesia, mathematics is one of the major subjects in primary up to secondary school. It aims to provide learners the ability of higher order thinking skills (HOTS). In order to measure the achievement of the objectives of mathematics learning, the government annually conducts the national examination for mathematics courses. It causes mathematics became one of subjects that is feared by most students and consequently make some teachers and students changed mathematics course â€œlearning objectivesâ€ from reaching HOTS to just passing the national examinations. So, many unreliable quick ways emerge to solve the math problems. Some of the ways sometimes led to misconceptions in mathematics, which would obstruct the ability of the studentsâ€™ HOTS. This article aims to show some of the misconceptions that are often encountered in solving mathematics problems. By recognizing the misconceptions, teachers are expected to avoid them and optimally anticipate the achievement of the â€œtrueâ€ objectives of learning mathematics.